Os dispositivos de vigilância em sites de redes sociais digitais como estratégia de comunicação organizacional: análise da ambiência da Universidade de Santa Cruz do Sul no site de rede social facebook - Moreira, Elizabeth Huber (2017)
The proposal of this research is to comprehend how the University of Santa Cruz do Sul uses the surveillance devices of the mediated interactions through the digital social network website Facebook as surveillance exercise of the organizational setting in a strategic way. Theory studies were performed about the digital social networks in the context of the communication in the companies; about the power and the surveillance in the communication of the companies; and about the strategic communication in the companies. To empirically analyze this phenomenon, a research was performed in the University of Santa Cruz do Sul, which is an institution of higher education localized in the region of Rio Pardo Valley, in the state of Rio Grande do Sul, Brazil. As methodological procedures a CMDA – Computer-Mediated Discourse Analysis approach was used, proposed by the American researcher Susan Herring (2004, 2007, 2013) for analysis of posts of the University of Santa Cruz do Sul in its setting on the social network website Facebook, as well as the comments of Internet users, during the months of May, June, July, August and September of 2015. Also, techniques of interview were used with the coordinator of the Marketing and Communication Advisory and with the social media strategist of Unisc in order to analyze the surveillance exercise and the strategic use of information about the institution which surrounds the digital social networks and document analysis of the university planning documents where the communication field is recorded. Through the research, it was noticed that the university pursues the users’ information, especially the detractors’ ones, and that when the university shows its presence the users change their discursive behavior, such questions that characterize the surveillance exercise, however it was verified that there is not a database which stores the collected information. It was also possible to verify that the surveillance exercise is not configured as a strategy of organizational communication, because there is not planning for the work which is developed on Unisc fanpage on the social network website Facebook and that the way of proceeding depends much on the intuition of the social media strategist.